2008
DOI: 10.1007/s11211-008-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-Hurricane Katrina Racialized Explanations as a System Threat: Implications for Whites’ and Blacks’ Racial Attitudes

Abstract: This experiment drew upon theoretical perspectives on group and system justification to examine whether exposure to media coverage arguing that racism was responsible for the ineffective Hurricane Katrina disaster response affected White and Black Americans' intergroup attitudes. Consistent with a system justification perspective, Whites exposed to video clips arguing that the hurricane Katrina disaster response was due to racism displayed greater racial ingroup attachment and ingroup love compared to Whites e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…The results of this meta-analysis extend the theoretical and experimental evidence on the relationship between threats to justice and just-world beliefs. Specifically, the findings reported here demonstrate that the relationship between perceived injustice and bolstering of one's belief system (Hafer, 2000;Heine et al, 2006;Jost et al, 2003;Kaiser et al, 2008;Kay et al, 2007;Solomon et al, 2004) is reflected in societal-level trends across time. This ability to extend findings from the laboratory setting further demonstrates the relevance and predictive power of psychological theory and science for naturalistic contexts and events.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The results of this meta-analysis extend the theoretical and experimental evidence on the relationship between threats to justice and just-world beliefs. Specifically, the findings reported here demonstrate that the relationship between perceived injustice and bolstering of one's belief system (Hafer, 2000;Heine et al, 2006;Jost et al, 2003;Kaiser et al, 2008;Kay et al, 2007;Solomon et al, 2004) is reflected in societal-level trends across time. This ability to extend findings from the laboratory setting further demonstrates the relevance and predictive power of psychological theory and science for naturalistic contexts and events.…”
Section: Discussionmentioning
confidence: 60%
“…For example, laboratory studies have shown that when people encounter injustice, such as innocent victims of crime, they become preoccupied with thoughts about justice (Hafer, 2000; see also Kay & Jost, 2003). Additionally, after threats to their beliefs, people show stronger adherence to their beliefs via increased support of others who share their worldview (i.e., ingroup bias) (Kaiser, Eccleston, & Hagiwara, 2008;McGregor, Zanna, Holmes, & Spencer, 2001;Solomon, Greenberg, & Pyszczynski, 2004). Likewise, when strong endorsers of just-world beliefs encounter evidence that threatens the legitimacy of their beliefs, they report being more strongly committed to those beliefs compared to when those beliefs are not threatened (Kay et al, 2007).To achieve this commitment to their beliefs, people often fortify their belief systems by re-construing perceived injustice as equitable through psychological compensatory means.…”
Section: Belief In a Just Worldmentioning
confidence: 99%
“…de Dreu (2010) similarly found that individual differences in pro-social (compared with pro-self) orientation determined self-sacrificing for the benefit of the ingroup, but not penalizing of outgroup members. In other areas, adversarial groups in political or ethno-religious conflict tend to attribute their own group's aggression to ingroup favoritism more so than outgroup hostility, whereas aggression from outgroup members is attributed more to outgroup hostility toward the perceivers' group (Kaiser, Eccleston & Hagiwara, 2008;Waytz, Young & Ginges, 2014). And finally, genetic (Lewis & Bates, 2014), neurological (Baumgartner, Schiller, Rieskamp, Gianotti & Knoch, 2014) and developmental (Buttelman & Böhm, 2014) markers of ingroup favoritism, as distinct from outgroup hostility, have also recently been documented.…”
Section: Favoritism Hostility and Multiculturalismmentioning
confidence: 99%
“…This study reveals that disaster damage causes more federal expenditures for disabilities in Alabama, Florida, Louisiana, and Texas. Numerous studies, especially after Hurricane Katrina, have shown that racial and ethnic communities in the United States are more vulnerable to natural disasters (Bullard, 2008;Carp, 2007;Cline et al, 2010; M. L. K. Edwards, 1998;Elliott & Pais, 2006;Forgette et al, 2008;Fothergill et al, 1999;Hobfoll, 2012;Kaiser et al, 2008;Uttley, 2010;Wiener, 2007;Wisner & Luce, 1993;Wyche et al, 2011). The result of this study showed that Black populations are more socially vulnerable to natural disasters in Florida, Mississippi, and Texas.…”
Section: Relationship Of Results To Previous Findingsmentioning
confidence: 57%
“…Race and ethnicity, are related to structural conditions, such as educational and employment prospects, the organization of family and kin systems, cultural preferences that shape an individual's worldview which subsequently influences how people perceive stressful events, view their need for support, and recognize resources that they deem appropriate for managing their circumstances (Carp, 2007;Cline et al, 2010;M. L. K. Edwards, 1998;Elliott & Pais, 2006;Forgette et al, 2008;Hobfoll, 2012;Kaiser, Eccleston, & Hagiwara, 2008;Wyche et al, 2011).…”
Section: Ethnic Minoritiesmentioning
confidence: 99%